Sexual Values and Risky Sexual Behaviors Among Latino Youths - Deardorff, Julianna (2010)
CONTEXT: Understanding Latino youths’ sexual values is key to informing HIV prevention efforts. Few studies have examined associations between culturally based sexual values and behaviors among Latinos. METHODS: A sample of 839 sexually active Latinos aged 16–22 residing in San Francisco were interviewed in 2003–2006. Multiple regression and multinomial logistic regression analyses were conducted to examine associations between sexual values and behaviors, while adjusting for language use (a proxy for acculturation) and other covariates. RESULTS: The importance attached to female virginity was negatively associated with the number of sexual partners women had had in their lifetime (odds ratio, 0.8) and in the past year (0.9), and was positively associated with women’s nonuse of condoms, rather than consistent use, during the first month of their current relationships (1.8). For men, the importance of satisfying sexual needs increased with the numbers of lifetime and recent sexual partners (1.4 and 1.1, respectively), and with inconsistent condom use in the first month of their relationships (1.9). Comfort with sexual communication was positively associated with inconsistent use or nonuse of condoms in the last month of both men’s and women’s current relationships (2.0–2.2). For women, considering satisfaction of sexual needs important was associated with more sexual partners only among those who attached little value to female virginity. CONCLUSIONS: It is important to integrate themes of virginity and sexual desire into intervention curricula so youth can better understand how these sexual norms influence their developing sexual identities and behaviors.